PATIENTS’ SELF-PERCEPTION, ATTITUDES AND AWARENESS OF HEALTH RISK FACTORS (PATIENTS’ JUDGMENT OF RISKS) - LAZA, Valeria; MUSTATA, Maria; CONSTANTINIUC, Mariana (Studia Universitatis Babeş-Bolyai Bioethica, 2017)
The construction of risk perception is important, because perception has a great inertia, and it shapes the attitudes and the human behavior. Ill people are more vulnerable and susceptible than healthy people, their coping and resilience strategies being jeopardized by emotional determinants. Methods. An anonymous questionnaire including items about the reason/ reasons for hospital admission, diagnosis at admission, and questions with multiple-choices answers trying to detect patients’ perception on their health and the awareness of risk factors conditioning the health status was used on 200 patients hospitalized in three clinics: Infectious Diseases, Occupational Medicine and Medical Clinic. Results. Demographic and socio-economic structure of patients differ form one clinic to another. Although among the first three sources of information frequently accessed, internet is on the last place when it comes on confidence. Most trustful are doctors, then TV and friends, the least trustful being radio, magazines and internet. Patients’ attitudes and awareness of health risk factors reflect their knowledge and a discrepancy between attitudes and behavior. Many of presented results in ill people are similar to healthy people, but in terms of disease perceived risk, patients are much more influenced by their level of knowledge and socio-economic level, and other unconscient motivational factors, conducting to an underestimation of risk. Conclusions. Patients’ health education in hospitals is important, but Romania nowadays is confronting a severe shortage of medical staff, so further and refined research is needed to better and fully understand the factors underlying risk perception in ill people. REZUMAT. Auto-percepția pacienților, atitudinile și conștiința cu privire la factorii de risc în sănătate (judecata riscurilor în percepția pacienților). Construirea percepției asupra riscului este importantă, deoarece percepția are o mare inerție și formează atitudinile și comportamentul uman. Oamenii bolnavi sunt mai mult vulnerabili decât oamenii sănătoși, coping-ul și strategiile de reziliență fiind periclitate de factorii emoționali. Metode. Un chestionar anonim care conține elemente despre motivul / motivele internării la spital, diagnosticul la internare și întrebări cu opțiuni posibile de răspunsuri încearcă să detecteze percepția pacienților asupra sănătății lor, fiind utilizată conștientizarea factorilor de risc care condiționează starea de sănătate la 200 de pacienți internați în trei clinici: Boli Infecțioase, Medicina muncii și Clinică medicală. Rezultate. Structura demografică și socio-economică a pacienților diferă de o clinică la alta. Printre primele trei surse de informații frecvent accesate, internetul este pe ultimul loc când vine vorba de încredere. Cei mai de încredere sunt doctorii, apoi televiziunea și prietenii, încrederea cea mai redusă o au în radio, reviste și internet. Atitudinile pacienților și conștientizarea factorilor de risc pentru sănătate reflectă cunoștințele lor, fiind evidentă o discrepanță între atitudini și comportament. Rezultatele percepției la pacienți sunt similare cu cele ale persoanelor sănătoase, dar în termeni de percepție a riscului de boală, pacienții sunt influențați de nivelul de educație, de cel socio-economic, și de factorii motivaționali, fapt ce duce la o subestimare a riscului. Concluzii. Educația pacienților cu privire la sănătate în spitale este importantă, dar România zilelor noastre se confruntă cu o lipsă severă de personal medical, este nevoie de cercetare atentă pentru a înțelege mai bine factorii care stau la baza percepției riscului de boală. Cuvinte-cheie: percepția riscului, pericol, atitudini, comportamentul pacienților, mediu